Ernesta Foldāta albums ar diplomiem un ilustrācijām - Kuzņecova, Kristīne (My University, 2020)
Latvijas Universitātes Goda doktora, Latvijas Zinātņu Akadēmijas Ārzemju Goda locekļa, Venecuēlas Centrālās Universitātes un Nacionālo parku institūta emeritētā profesora, orhideju pētnieka Ernesta Foldāta (1925-2003) albūms ar saņemtajiem diplomiem, sertifikātiem un orhideju attēliem.
Ernest Foldat's album with diplomas and illustrations
Album with received diplomas, certificates and pictures of orchids by Ernest Foldat (1925-2003), a professor emeritus at the Central University of Venezuela and the Institute of National Parks of the University of Latvia, an honorary doctor of the Latvian Academy of Sciences, an honorary member of the Latvian Academy of Sciences.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Latvijas Universitātes Muzejs; Orchidaceae; orhidejas; Venecuēla; botany; Research Subject Categories::NATURAL SCIENCES::Biology